(untitled) (Comunicação & Inovação, 2017)
In the last few decades, civil society organizations have been prominent in the debates regarding topics of public interest by demanding the government greater social participation in the implementation of public policies. One of these organizations is the National Forum for the Democratization of Communication in Brazil (FNDC), a civil society organization founded 25 years ago that aims to create means for dialogue with the government in order to achieve progress on the agenda of media democratization. Based on a bibliographical research and on the analysis of FNDC documents, this article analyzes how the subject of media democratization has been addressed by the organization after the 1st Brazilian Conference on Communications (Confecom). The main concepts used for our study were public space and social participation. Our research points out that, albeit it has promoted public debate on the subject, FNDC has not been able to achieve a degree of dialogue with the government that would result in changes for the sector.